1983
DOI: 10.1021/jm00360a001
|View full text |Cite
|
Sign up to set email alerts
|

New developments in calcium ion channel antagonists

Abstract: Toward the beginning of this Perspective we posed a number of questions to be answered concerning the Ca2+ channel antagonists. Biochemical, chemical, clinical, pharmacological, and physiological studies collectively support the conclusion that this important group of molecules does function in specific fashion to inhibit Ca2+ channel function. Major questions of mechanisms and sites of action remain, however, to be resolved. The recent radioligand binding assay supports the conclusion, drawn earlier from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
177
0
5

Year Published

1985
1985
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(185 citation statements)
references
References 32 publications
3
177
0
5
Order By: Relevance
“…The increase in the [Ca 2ϩ ] i transient elicited by combined AMPA͞IDRA-21 (Fig. 3) or AMPA͞cyclothiazide treatments (data not shown) were also considerably reduced by nitrendipine, a blocker of L-type-voltage-sensitive calcium channels (VSCC) (27). Such nitrendipine pretreatment also reduced by Ϸ50% the neuronal death induced by 25 (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The increase in the [Ca 2ϩ ] i transient elicited by combined AMPA͞IDRA-21 (Fig. 3) or AMPA͞cyclothiazide treatments (data not shown) were also considerably reduced by nitrendipine, a blocker of L-type-voltage-sensitive calcium channels (VSCC) (27). Such nitrendipine pretreatment also reduced by Ϸ50% the neuronal death induced by 25 (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…We observed that the [Ca 2ϩ ] i transient but not the [Na ϩ ] i transient increase elicited by application of AMPA͞IDRA-21 is reduced (by 60-70%) when the cells are exposed to the blocker of VSCC nitrendipine (27). At a dose of 1 M, nitrendipine reduces by Ϸ50% AMPA plus cyclothiazide-induced neurotoxicity, suggesting that the time-course of the [Ca 2ϩ ] i transient increase elicited by application of AMPA͞IDRA-21 or AMPA͞ cyclothiazide is at least in part indirectly mediated by the opening of L-type VSCC triggered by the neuronal depolarization caused by a Na ϩ influx occurring via AMPA receptor activation.…”
Section: Discussionmentioning
confidence: 79%
“…Dot-like traces show the cells with only active rotation. Among the calcium channel blockers, cinnarizine and nicardipine 15 ) induced the change in swimming behavior. As in the case of the calmodulin antagonists, the cells swam forwards again after a few more minutes of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Drugs that block these voltagedependent Ca 2+ channels are used for the treatment of various cardiovascular disorders and are referred to as Ca 2+ channel antagonists (4)(5)(6)(7)(8). Nifedipine, nitrendipine, nisoldipine, and related 1,4-dihydropyridines are the most potent class of Ca 2+ channel antagonists, and radiolabeled dihydropyridines have been shown to bind with high affinity to membranes isolated from cardiac, skeletal, and smooth muscle (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%